Exploring the Relationship Between Social Ties and Resilience From Evolutionary Framework - Agashe, Sayli; Kumar, Sunil; Rai, Rishabh (Frontiers in Human Dynamics, 2021)
This conceptual paper examines the necessity and importance of social bonds and networks in building resilience to fight the COVID-19. Resilience is a quality that energizes an individual’s actions and acts as a buffer to stressful events. The current article is intended to explore the evolutionary programmed behavior of the human mind to make social ties and structure. Humans have a strong need to connect and relate with other individuals by developing cooperation and perspective-taking. The ability to make social connections, group living, and sharing resources had a selective advantage in coping with physical and psychological stress. Social bonds provide resilience to people’s approach while making adjustments and adapting to situations, thus presents fitness benefits at both group and individual levels. An attempt has also been made to address how social isolation as a strategy to contain the infection adversely influence body homeostasis. Finally, this article recommends health practitioners, clinicians, and researchers to encourage research on the impact of social isolation/social interaction on mental and physical health indicators.